PENINGKATAN STATUS GIZI BALITA MELALUI PEMBERIAN DAUN KELOR (MORINGA OLEIFERA) - Nuraina Nuraina; Agus Susanti; Munawwarah Munawwarah; Manisa Salaila; Izzatul Muna; Noratul Ikram; Dessiana Dessiana; Hasratina Hasratina; Tasnim Miska; Nadia Urizky; Nisaul Khaira (LPPM Universitas Al Muslim, 2022)
Stunting is a nutritional problem that must be immediately prevented and treated in Indonesia in order to produce a smart and quality generation. The government is working to accelerate the reduction in the stunting rate in Indonesia by issuing Presidential Regulation of the Republic of Indonesia Number 72 of 2021 concerning accelerating the reduction of stunting. The results of the initial survey and discussion with the village midwife of Cot Rabo Baroh found that 5 (five) toddlers were stunted. Stunting that occurred in Cot Rabo Baroh Village was caused by a lack of knowledge of the community, especially parents, about fulfilling nutrition in toddlers. This activity is carried out by socialization, counseling and evaluation methods. Education about Moringa leaf nutrition and how to give Moringa leaves to toddlers which aims to provide an understanding to the public about the benefits of giving Moringa leaves to stunting toddlers to fulfill their daily life nutrition. The results of the service showed a significant change in knowledge before and after being given counseling. The majority of pretest results were in the poor category as many as 10 people with a percentage of 33.33%. While the majority of the posttest results were in the good category as many as 15 people with a percentage of 50%. It is hoped that after this community service activity the stunting toddler case will be resolved in Cot Rabo Baroh Village.